PERLINDUNGAN HAK CIPTA TERHADAP PENAYANGAN IMPERFECT THE SERIES OLEH AKUN TIKTOK - Vanessa Jaya Arlandy; Dian Purnamasari (Reformasi Hukum Trisakti, 2021)
The case of Imperfect the Series airing by TikTok account resulted in a considerable number of viewers. the action was done without the knowledge of Ernest Prakasa, as the creator. Problem formulation: whether the viewing of Imperfect the Series by TikTok account is an act of copyright infringement and how efforts can be taken by Ernest Prakasa in overcoming the viewing of Imperfect the Series by TikTok account. the research method used is normative, the nature of the research is descriptive, using secondary and primary data. Based on the results of research, discussion and conclusions, that the viewing of Imperfect the Series is an act of copyright infringement, which violates moral rights and economic rights, as stipulated in Article 1 number 17, Article 1 number 12, and Article 5 paragraph (1) UUHC. In addition, the effort that can be taken by Ernest Prakasa is to reprimand the account and file a report. These efforts are in accordance with the applicable procedures and provisions. If these efforts are unsuccessful, then the efforts that can be taken are through alternative dispute resolution channels or courts, based on Article 95 paragraph (1) UUHC.